Medical Waste Management Innovation Based on Thermal and Chemical Degradation of Polymers - Ilyu 'Ainun Najie'; Muhammad Dary Adhidrawa Margolang; Muhammad Diaz Supandi; Keysa Najmi Tsaqib; Niken Sylvia Puspitasari (Jurnal Ners, 2026)
The massive growth of healthcare services, particularly post-COVID-19, has significantly increased volumes of hazardous polymer-based and infectious medical waste. Conventional methods like open incineration pose environmental and health risks due to toxic emissions and incomplete sterilization, highlighting an urgent need for safer, efficient, and sustainable management innovations. This study analyzes the effectiveness of thermal (pyrolysis, gasification) and chemical (depolymerization, Advanced Oxidation Processes/AOPs) degradation technologies through qualitative library research. Data from credible sources (indexed journals, WHO/UNEP reports, government policies; 2018–2025) were descriptively-critically and comparatively analyzed. Results demonstrate that controlled thermal degradation reduces waste volume by 90%, neutralizes pathogens at 400–800°C, and converts waste into valuable products (syngas, bio-oil), while chemical approaches (catalysts, AOPs) decompose polymers at the molecular level and neutralize heavy metals/organic contaminants without dioxin emissions. Integrating both technologies via capacity-based regional clustering and blended finance schemes proved technically-economically feasible. Contributions include: (1) Policy recommendations for the Ministry of Health/Environment to standardize green technologies; (2) Technology-as-a-Service business models for healthcare facilities; (3) Collaborative implementation frameworks (government-private-academia) supporting SDGs and Indonesia’s 2045 Golden Vision through pollution prevention, circular economy, and improved public health outcomes